LncRNA NBR2 Regulates Cancer Cell Stemness and Predicts Survival in Non-small Cell Cancer Patients by Downregulating TGF-β1 - Huang, Jun; Yu, Qiuhua; Zhang, Junjie; lu, Wenbin; Liu, Qian; Chu, Ying; Zhou, Yanjuan; Tu, Renshu; Zhou, Huxiang; Wang, Qiang (Current Pharmaceutical Biotechnology, 2023)
Background: LncRNA NBR2 is a key regulator in cancer metabolism. However, its role in lung cancer is unknown. Objective: This study aimed to explore the function of NBR2 in non-small cell lung cancer (NSCLC), which is the most common type of lung cancer. Methods: Paired NSCLC and non-cancer tissues were collected from 68 patients with NSCLC. The expression of NBR2 and transforming growth factor-β1 (TGF-β1) in these samples was analyzed by RT-qPCR. The prognostic value of NBR2 for NSCLC was explored by performing a 5-year follow-up study. The interaction between NBR2 and TGF-β1 in two NSCLC cell lines was detected by overexpression assay, followed by RT-qPCR and Western blot analysis. Flow cytometry was performed to evaluate the role of NBR2 and TGF-β1 in regulating NSCLC cell stemness. Results: NBR2 was significantly downregulated in NSCLC tissues than that in non-cancer tissues of NSCLC patients, and low expression levels of NBR2 predicted poor survival. TGF-β1 was significantly upregulated in NSCLC tissues than that in non-cancer tissues, and was inversely correlated with NBR2. Overexpression of NBR2 downregulated TGF-β1, while overexpression of TGF-β1 did not affect the expression of NBR2. Overexpression of NBR2 inhibited, while overexpression of TGF-β1 promoted NSCLC cell stemness. Overexpression of TGF-β1 attenuated the effects of overexpression of NBR2. Mechanically, NBR2 interacted with Notch1 protein to inhibit its expression, thereby inhibiting the expression of TGF-β1 and further affecting the proportion of CD133+ cells. Conclusion: LncRNA NBR2 regulates cancer cell stemness and predicts survival in NSCLC possibly by downregulating TGF-β1 through Notch1.
Keywords: Non-small cell lung cancer